Pengaruh Data Video Streaming pada Kinerja Protokol Optimized Link State Routing (OLSR) menggunakan Teknologi Wireless Mesh Network - Shindy Maria Ulfa; Rakhmadhany Primananda; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the past few years, streaming media has been enhanced within the wireless network, which is known as wireless mesh network. There is challenge if streaming connected through WMN, which is caused that streaming application requires broad bandwidth for high speed data within multi-hop media as well, thus produces packet value loss and delay significantly, while the streaming depends on packet loss and delay. That is why the purpose of this research is to figure the effect of streaming on optimized link state routing performance using wireless mesh network technology. As for the parameters used to know streaming quality in the network are; delay, packet loss, throughput and jitter. The testing has been done through some scenarios, which are; connection amongst client - server, streaming testing within 1 Mbps bandwidth, streaming testing within 2 Mbps bandwidth. The testing result of those scenarios deliver the highest throughput value as 928 kbps, value of the smallest delay is produced as 12.6 ms, the lowest jitter value as 0.0000098ms, produces packet loss value as 0.00018%. Based on the testing result, thus video streaming occurs on optimized link state routing performance using wireless mesh network technology shows a very good result.